Three-dimensional evaluation of murine ovarian follicles using a modified CUBIC tissue clearing method - Kyosuke Kagami; Yohei Shinmyo; Masanori Ono; Hiroshi Kawasaki; Hiroshi Fujiwara (BMC, 2018)
Abstract Background Recently, we demonstrated the three-dimensional (3D) localization of murine trophoblast giant cells in the pregnant uterus using a modified Clear Unobstructed Brain Imaging Cocktails and Computational analysis (CUBIC) tissue-clearing method and hybrid construct consisting of the cytomegalovirus enhancer fused to the chicken beta-actin promoter (CAG) conjugated enhanced green fluorescent protein (EGFP) transgenic mice. In this study, we applied this method to obtain a transparent whole-image of the ovary and observed the 3D localization of individual oocytes in the developing follicles. Methods Ovarian samples were obtained from EGFP transgenic mice and subjected to nuclear staining with propidium iodide (PI) and CUBIC treatment. The detection of double fluorescence signals (green and red) and subsequent reconstruction of 3D images of the whole ovary were performed by light-sheet microscopy and computer programs, respectively. Results The ovary became transparent using the CUBIC method and each nucleus of the follicle component cells was uniformly fluoro-stained by PI perfusion. In contrast, EGFP signals were strong in oocytes, whereas those of surrounding granulosa cells were faint. These signal differences in EGFP expression among oocytes, granulosa cells, and theca-interstitial cells produce well-contrasted images of the growing follicles, providing clear information of the 3D localization of individual oocytes. Conclusion These results indicate that this procedure is one of the effective approaches to analyze the 3D structure of follicles in the whole ovary.